PARTY POWER AND LEGISLATIVE DYNAMICS IN THE SOUTH KOREAN NATIONAL ASSEMBLY - Sanjar Yakhshilikov (Ecominds Press, 2025)
This paper examines the core role of political parties in influencing legislative politics in the National Assembly of South Korea. Based on institutional and electoral politics, legislative committees, and contemporary political phenomena, it explores the role of party constellations in shaping lawmaking outcomes. This study focuses on the dominance of the Democratic Party and the People Power Party, the political importance of negotiation groups, and the procedural advantage of majority blocs. Supported by cases related to legislative deadlock, committee proportionality, and major legislative reforms, this paper argues with evidence that legislative output and policy agenda-setting in South Korea are dominated much more by strongly disciplined party teams rather than legislator-level decision-making. Evidence from this paper shows that despite legislative design principles aimed at ensuring a proper sharing-of-power arrangement for minorities within a majority governance situation, the actual politics in the National Assembly live with fluxes of power positions, political party rivalries, and leadership-driven politics with party control standing out most prominently as the key political activation force within the South Korean legislature.
Keywords: South Korean National Assembly, political party influence, legislative gridlock, party discipline and negotiation groups, committee politics.